Inequalities in adolescent mental health and allocation of students to selective classes in comprehensive schools in Finland: a longitudinal study - Kesanto-Jokipolvi, Heidi; Siipola, Mari; Koivuhovi, Satu; Pasu, Terhi; Seppänen, Piia; Rimpelä, Arja (BMJ Publishing Group, 2025)
BACKGROUND: Lower socioeconomic positions (SEP) and poor academic achievement increase children's risk for mental health problems. The Finnish education system is officially non-selective and unified, but a part of children can be selected into emphasised teaching classes by aptitude tests, which are known to segregate students by SEP and academic achievement. We study here if allocation of students to mainstream and selective classes segregates students by mental health, too.
METHODS: Students from primary school (6th grade) were followed to lower secondary school (7th grade). The number in selective classes was n=209 and in mainstream classes n=551. Outcomes were depressed mood, anxiety and daily health complaints. Association between class type and the outcomes was analysed by cross-tabulation and logistic regression models. Gender, academic achievement, SEP and previous mental health were independent and confounding/moderating variables.
RESULTS: Students in selective classes had better academic achievement and higher SEP compared with students in mainstream classes. Girls reported poorer mental health than boys. Depressive mood did not vary by class type, but anxiety and daily health complaints were more common among girls in mainstream classes. When academic achievement and background factors were considered, among girls only anxiety was more common in mainstream classes, but among boys, anxiety appeared to be statistically significantly more common in selective classes.
CONCLUSION: Grouping students by aptitude tests to different classes may select them by mental health, too. Longer follow-up and gender-specific studies would give more reliable answers for education policy makers about student grouping by aptitude test and its effects on segregation.